(untitled) (Research, Society and Development, 2020)
This work aims to present the results of a didactic proposal using art as an ally and pedagogical resource in the teaching-learning process, developed in the first year of the Integrated Technical Course in Agriculture during the discipline Soils and Fertility. The methodology of this research is based on Freire’s dialogical educational conception with the objective of providing meaningful learning to students. The student had access to the introductory knowledge of Soil Science (soil concept; soil formation factors; soil properties: texture and color), experienced stages of the construction of scientific knowledge, had contact with aspects of the soil formation process and this trajectory was mediated by art, which stimulated autonomy in the learning process and contributed to the formation of the subject in an educational-creative process. Therefore, we suggest that it serves as a stimulus for teachers to use art as a didactic resource in scientific learning in a playful and creative way.